MOTIVASI BONUS PLAN DALAM FRAUDELENT FINANCIAL STATEMENT - Adhikara, MF. Arrozi (Lembaga Penerbitan Unversitas Esa Unggul, 2020)
This study to examine the elements of fraud in the Pentagon fraud theory indetecting fraudulent financial statements. Fraud pentagon is proxied by six variables consisting of two elements of pressure (financial target and external pressure), one variable from element opportunity (ineffective monitoring), one variable from element rationalization (change in auditor), one variable from capability element (change in directors) ), and one variable from the arrogance element (number of CEO's pictures) hypothesized to affect fraudulent financial statements. F-Score is used to determine the fraudulent financial statement with bonus plan based earnings management as an intervening variable. This study with a sample of 35 companies was selected using a purposive sampling method from delisting companies in the Indonesia Stock Exchange in 20092016. Hypothesis testing uses a path analysis to test the Effects of Pressure, Opportunity, Rationalization, Competence, and Arrogance Against the Fraudulent Financial Statement with Earning Management Based on Bonus Plans as Intervening Variables on Companies Delisting on the Indonesia Stock Exchange 2009-2016.The results showed that ROA, DER, RKI had a positive effect on earnings management. While earnings management has a negative effect on fraudulent financial statements. DER and CEO have a negative effect on fraudulent financial statements and CPA has a positive effect on fraudulent financial statements.Â Keywords : fraudulent financial statement, pressure, opportunity,Â rationalization, competence, arrogance, earning management, bonus plan